Kajian Bentuk, Fungsi dan Makna Upacara Nangkluk Mrana di Pantai Pura Segara Kecamatan Negara Kabupaten Jembrana - Adi Prastya, I Putu (Metta : Jurnal Ilmu Multidisiplin, 2021)
Hindus in Negara Subdistrict, Jembrana Regency, carry out the Nakluk Mrana Ceremony regularly according to the stipulated time, regardless of whether or not pests or diseases are endemic. The Nangkluk Mrana ceremony is a medium for appealing to Ida Sang Hyang Widhi Wasa as the ruler of the universe and all its contents, to provide safety, happiness and prosperity in life. The aim of this research is: To find out the reasons for carrying out the Nangluk Mrana ceremony, the procession, function and meaning of the Nangluk Mrana Ceremony for the people of Negara District, Jembrana Regency. Meanwhile, the benefits of the research are expected to be an academic contribution in adding theory and developing concepts related to the Bhuta Yadnya ceremony, including the Nangkluk Mrana Ceremony which is carried out by Hindus. The results of research regarding the Nangluk Mrana Ceremony at Pura Segara Beach were carried out by the people of Negara Subdistrict, Jembrana Regency on the grounds that there was a disease outbreak attacking the people of Negara, to neutralize Mrana, the form of the Nangluk Mrana Ceremony at Pura Segara Beach, Negara Subdistrict, Jembrana Regency includes the stages of the Nangluk Mrana Ceremony procession including : (1) Preparation for the Ceremony, (2) creation of facilities and infrastructure for the Nangluk Mrana Ceremony. (3) Implementation of the Peak of the Nangluk Mrana Ceremony. The functions of the Nangkluk Mrana Ceremony at Pura Segara Beach, Negara District, Jembrana Regency are: (1) mrana repellent function, (2) anticipatory function, (3) economic function, (4) socio-cultural function, (5) religious function, while the meaning contained in the Nangluk Mrana Ceremony is the meaning of prosperity, meaning that through the Nangluk Mrana ceremony the harvest will increase so that it can improve the welfare of society, the meaning of integration is that through the Nangluk Mrana ceremony it will bring about an attitude of mutual cooperation from all levels of society, so that a sense of unity in ngayah is fostered, while the meaning of balance is that through the implementation of the Nangluk Mrana ceremony we will be able to protect the environmental ecosystem and maintain a balance between the relationship between humans and God, humans and humans and humans and the natural environment so that Jagadhita Ya Ca Iti Dharma can be realized.